Anatomical-morphological, histological and immunohistochemical features of the cardiovascular system of the intact white rats - Shevchuk , M.M. (Морфологія / Morphologia / Morfologìâ, 2026)
Background. The rat heart is one of the standard objects in experimental studies that model human cardiovascular pathologies. The high degree of homology of the mammalian heart structure allows the use of the results of morphological studies for comparative anatomy and pathophysiology. Objective: To study the anatomical-morphological, histological, and immunohistochemical features of the cardiovascular system of intact laboratory white rats. Methods. Experimental studies were conducted on 10 sexually mature white non-linear male rats weighing 180-230 g. During the 10 days of quarantine, daily observations were made of the appearance, behavior, food intake and general condition of the animals. After preparation, rat heart tissue was fixed in 10% buffered formalin solution, followed by alcohols of increasing concentration and paraffin embedding according to standard protocols. Then, histological sections with a thickness of 5±1 μm and semi-thin sections with a thickness of 1 μm were prepared. Immunohistochemical studies were performed using monoclonal antibodies for vascular endothelium CD31 (Clone JC70A, Thermo Fisher scientific). Visualization of IGH reactions was performed using the DAKO EnVision+System detection system with diaminobenzidine chromogen. Morphometry of rat heart vessels, in particular their diameters and wall thickness, was performed using Aperio ImageScope v12.3.3 software (Leica biosystems, Wetzlar, Germany). Results. The anatomical and morphological features of the heart of laboratory white male rats under normal functional conditions are considered. A detailed description of the macroscopic structure of the heart is given, the histological structure of the heart muscle, endocardium, pericardium and heart vessels is investigated. The results of macroscopic and histological studies of the structure of the heart muscle, endocardium, pericardium and vascular network of the heart supplement data on the norm of the cardiovascular system, which is important for fundamental and experimental cardiology, as well as for the assessment of pathological changes in models of cardiovascular diseases. Immunohistochemical and morphometric analysis confirmed that in the myocardium of intact rats the vascular bed is represented by arteries of various calibers, arterioles, a dense capillary network and venous vessels. The arterial wall had a clearly expressed intima, media and adventitia. Arterioles were characterized by thin but clearly defined media, while venules had thin walls with a minimal muscular component. The combination of histological description of vessels with morphometry creates a reliable basis for further control–experimental comparisons. In rat myocardium, uniform expression of CD31 reflects the integrity of the vascular endothelial layer and the absence of inflammatory or dystrophic damage. The obtained indicators can serve as a reference morphological basis for experimental studies of cardiovascular pathology. Conclusion. The identified features of macro- and microscopic organization and morphometric parameters of the vascular bed of the heart are important for establishing a reference basis and subsequently for comparison with the detected changes obtained in experimental models of induced pathologies.